Gel electrolyte and preparation method and application thereof

By adding low-melting-point succinate and fluoroether compounds to the gel electrolyte, combined with polymer monomers and lithium salts, a gel electrolyte with high conductivity and wide temperature range was prepared, solving the safety and low-temperature performance problems of traditional electrolytes and improving the overall performance of lithium-ion batteries.

CN121097196APending Publication Date: 2025-12-09WANXIANG 123 CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511290372.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-10
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Traditional liquid electrolytes are flammable, highly volatile, and pose a significant risk of leakage, while all-solid-state electrolytes have low ionic conductivity, which affects the safety and low-temperature performance of lithium-ion batteries.

Method used

A gel electrolyte was prepared by in-situ polymerization of low-melting-point succinate and fluoroether compounds as mixed additives, combined with polymer monomers and lithium salts, to improve lithium-ion transport rate and electrochemical stability and enhance low-temperature performance.

Benefits of technology

A gel electrolyte with high safety, high conductivity and wide temperature range has been developed, which enhances the overall performance of lithium-ion batteries and is suitable for existing battery manufacturing processes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a gel electrolyte and a preparation method and application thereof, and belongs to the technical field of secondary batteries. The gel electrolyte comprises the following raw materials: a polymer monomer, a liquid electrolyte, a mixed additive and an initiator, the mixed additive comprises butanedinitrile and a fluoroether compound; the liquid electrolyte comprises a lithium salt and an organic solvent. According to the gel electrolyte disclosed by the invention, the mixed additive is formed by mixing the succinonitrile and the fluoroether compound, has the characteristics of low melting point and low viscosity, and can be used for improving the low-temperature performance and wettability of the gel electrolyte and promoting room-temperature and low-temperature ion transmission.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of secondary batteries, in particular to a gel electrolyte and a preparation method and application thereof. BACKGROUND

[0002] Lithium ion batteries are widely used in consumer electronics, energy storage systems and electric vehicles due to their high energy density, long cycle life and high operating voltage. Among them, the electrolyte as the ion conduction medium plays a key role in the overall performance of the battery. Currently, traditional organic liquid electrolytes have problems such as flammability, high volatility, and high risk of leakage, while although the all-solid-state electrolyte has higher safety, its low ionic conductivity limits its practical application.

[0003] Gel lithium ion batteries are a kind of lithium ion batteries that use gel-state electrolytes instead of traditional liquid electrolytes. Gel batteries combine the advantages of liquid batteries and all-solid-state batteries, with extremely high safety and energy density. Therefore, developing gel electrolytes with high safety and high ionic conductivity has become a research focus.

[0004] Butanedinitrile is widely used in gel electrolytes due to its high dielectric constant and good lithium salt solubility. Patent document CN119133593A discloses a flame-retardant cross-linked PDOL gel electrolyte and its preparation method and application. A composite flame retardant is formed by coating a polymer matrix with halloysite nanotubes, and then mixed with 15wt%-25wt% butanedinitrile to achieve the purpose of plasticization and flame retardation. By adding a higher content of butanedinitrile, the electrochemical performance and safety of the gel electrolyte are optimized. However, butanedinitrile is in solid state at room temperature due to its high melting point, which affects its application in low temperature environments. Adding a large amount of butanedinitrile with a high melting point usually worsens the low temperature performance of the battery. SUMMARY

[0005] The present application aims to provide a gel electrolyte with low melting point and low viscosity; the present application also aims to provide a preparation method of a gel electrolyte with high ionic conductivity and wide temperature range; the present application also aims to provide an application of a gel electrolyte with high ionic conductivity and wide temperature range.

[0006] The present application discloses a gel electrolyte, the raw materials of the gel electrolyte include polymer monomers, liquid electrolyte, mixed additives, initiator; the mixed additives include butanedinitrile and fluorine ether compounds; the liquid electrolyte includes lithium salt and organic solvent.

[0007] The mixed additive contains succinonitrile and fluoroether compound. The succinonitrile with high polarity and high conductivity can improve the lithium ion transmission rate, and has good thermal stability and wide electrochemical window. The low viscosity and low melting point characteristics of the fluoroether compound are complementary to the succinonitrile to improve the ionic conductivity and low temperature performance of the gel electrolyte.

[0008] The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, and lithium perchlorate.

[0009] The polymer monomer includes at least one of vinyl, acrylate group in the structural formula of the polymer monomer.

[0010] The polymer monomer includes at least one of vinylidene fluoride, acrylonitrile, N-vinylpyrrolidone, methyl methacrylate, polyethylene glycol diacrylate, pentaerythritol tetraacrylate, triethylene glycol diacrylate, and polyethylene glycol methyl ether acrylate.

[0011] The organic solvent includes ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), methyl ethyl carbonate (DMC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC).

[0012] The initiator is one or a mixture of several of organic peroxide initiator and azo initiator, and the mass of the initiator accounts for 0.05-1.0% of the mass of the raw materials of the gel electrolyte.

[0013] Further, the mass of the mixed additive accounts for 1-10% of the mass of the raw materials of the gel electrolyte.

[0014] Further, the mass ratio of the fluoroether compound to the mass of the succinonitrile is 1:0.5-2.

[0015] When the mass ratio of the fluoroether compound to the mass of the succinonitrile is controlled in this range, the mixed additive exhibits low viscosity characteristics, thereby improving the wettability and ion transmission of the gel electrolyte, and the room temperature ion conductivity of the gel electrolyte at 25°C is ≥5 mS / cm. The low temperature performance of the mixed additive is excellent, and can improve the low temperature ion transmission of the gel electrolyte, and the ion conductivity at -10°C is ≥1 mS / cm.

[0016] Further, the fluoroether compound includes one or a mixture of several of 1,1,2,2-tetrafluoroethyl methyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0017] Further, the polymer monomer is an acrylate monomer.

[0018] Further, the polymer monomer comprises pentaerythritol tetraacrylate.

[0019] The pentaerythritol tetraacrylate has four functional groups (four polymerizable acrylate groups in one molecule), and can form a very dense and hard network structure, thereby improving the mechanical strength of the gel.

[0020] Further, the mass of the polymer monomer accounts for 2-50% of the mass of the raw material of the gel electrolyte.

[0021] Further, the organic solvent is a carbonate solvent.

[0022] The application further discloses a preparation method of the gel electrolyte.

[0023] S1: uniformly mixing an organic solvent, a lithium salt and a mixed additive to form a mixed solution;

[0024] S2: uniformly mixing the mixed solution with a polymer monomer and an initiator;

[0025] S3: performing a polymerization reaction on the mixed solution obtained in the step S2 to obtain the gel electrolyte as described above.

[0026] The gel electrolyte precursor containing succinonitrile additive provided by the application uses succinonitrile and a fluorine ether additive as a mixed additive. The high-polarity and high-conductivity succinonitrile can improve the lithium ion transmission rate, and has good thermal stability and a wide electrochemical window. However, the high melting point of succinonitrile leads to poor low-temperature performance. The fluorine ether can complement the succinonitrile, has high stability, low viscosity and low melting point, improves the wettability and conductivity, and makes up for the deficiency in low-temperature performance, so as to realize a high-conductivity gel electrolyte with a wide temperature range. In terms of process, the preparation method of the application is simple, and the in-situ polymerization reaction is performed in the battery through one-step injection, which is compatible with the existing battery production process and can be directly used in the existing battery production process.

[0027] The preparation method of the gel electrolyte disclosed in the application is simple, can be quickly dissolved through mixing, is compatible with the existing in-situ polymerization process, and can be directly applied to the existing battery production process. In addition, the mixed additive has inherent flame retardance, which has a potential positive effect on improving safety. Overall, the added mixed additive can significantly improve the inherent defects of the gel electrolyte in the prior art, and improve the comprehensive performance.

[0028] Further, in the step S3, the polymerization reaction is performed under the condition that the temperature is controlled at 40-75 DEG C and the time is kept for 6-24 hours.

[0029] The application further discloses a gel lithium ion battery comprising the gel electrolyte.

[0030] The application discloses a gel electrolyte, wherein a mixed additive is formed by mixing butanedinitrile and a fluorine ether compound, and the gel electrolyte has the characteristics of low melting point and low viscosity, can be used to improve the low-temperature performance and wettability of the gel electrolyte, and can promote ion transmission at room temperature and low temperature. DETAILED DESCRIPTION

[0031] In order to make the technical scheme of the application clearer, the application will be further described in detail below in combination with specific examples. In the examples, the experimental methods are all conventional methods unless otherwise specified, and the materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.

[0032] Example 1

[0033] The preparation method of the gel electrolyte specifically comprises the following steps:

[0034] Step S1: In an argon-filled glove box (moisture < 10 ppm, oxygen < 10 ppm), organic solvents ethylene carbonate (EC), methyl ethyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed, wherein the mass ratio of EC, EMC and DMC is 4:10:1. Then, lithium hexafluorophosphate, lithium bisfluorosulfonylimide salt, butanedinitrile and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are added to the organic solvents, and a magnetic stirrer is used for stirring at 500 rmp for 5-15 minutes. The mass fraction of lithium hexafluorophosphate in the raw materials of the gel electrolyte is 8%, the mass fraction of lithium bisfluorosulfonylimide in the raw materials of the gel electrolyte is 10%, and the mass fraction of the mixed additive in the raw materials of the gel electrolyte is 2%, wherein the mass ratio of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether to butanedinitrile is 1:1.

[0035] Step S2: After the lithium salt is completely dissolved, polymeric monomer pentaerythritol tetraacrylate and initiator azobisisobutyronitrile are added to the mixed solution, and the gel electrolyte precursor solution is obtained after sufficient stirring. The mass fraction of pentaerythritol tetraacrylate in the raw materials of the gel electrolyte is 4%, the mass fraction of azobisisobutyronitrile is 0.1%, the stirring speed is 500 rmp, and the stirring time is 30 minutes.

[0036] Step S3: The gel electrolyte precursor is placed in a polytetrafluoroethylene bottle and reacted at 70 DEG C for 8 hours to obtain an in-situ polymerized gel electrolyte.

[0037] Example 2

[0038] The preparation method of the gel electrolyte specifically comprises the following steps:

[0039] Step S1: In an argon-filled glove box (moisture <10 ppm, oxygen <10 ppm), organic solvent EC and diethyl carbonate (DEC) were mixed, wherein the mass ratio of EC and DEC was 4:1. Then, lithium hexafluorophosphate, lithium bisfluorosulfonylimide salt, lithium difluorophosphate, butanedinitrile, 1,1,2,2-tetrafluoroethyl ethyl ether were added to the organic solvent, and a magnetic stirrer was stirred at 500 rpm for 5-15 minutes. The mass fraction of lithium hexafluorophosphate in the raw materials of the gel electrolyte was 8%, the mass fraction of lithium bisfluorosulfonylimide salt in the raw materials of the gel electrolyte was 9%, the mass fraction of lithium difluorophosphate in the raw materials of the gel electrolyte was 0.5%, and the mass fraction of the mixed additive in the raw materials of the gel electrolyte was 3%; the mass ratio of 1,1,2,2-tetrafluoroethyl ethyl ether to butanedinitrile was 1:2.

[0040] Step S2: After the lithium salt was completely dissolved, the monomer triethylene glycol diacrylate and the initiator dimethyl azobis isobutyrate were added to the mixed solution, and the gel electrolyte precursor solution was obtained after sufficient stirring. The mass fraction of triethylene glycol diacrylate in the raw materials of the gel electrolyte was 5%, and the mass fraction of dimethyl azobis isobutyrate was 0.2%; the stirring speed was 500 rpm, and the stirring time was 30 minutes.

[0041] Step S3: Then, the gel electrolyte precursor was placed in a polytetrafluoroethylene bottle and reacted at 60°C for 12h to obtain an in-situ polymerized gel electrolyte.

[0042] Example 3

[0043] The preparation method of the gel electrolyte specifically includes the following steps:

[0044] Step S1: In an argon-filled glove box (moisture <10 ppm, oxygen <10 ppm), organic solvent EC, EMC and DMC were mixed, wherein the mass ratio of EC, EMC and DMC was 4:10:1. Then, lithium hexafluorophosphate, lithium bisfluorosulfonylimide salt, butanedinitrile, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether were added to the organic solvent, and a magnetic stirrer was stirred at 500 rpm for 5-15 minutes. The mass fraction of lithium hexafluorophosphate in the raw materials of the gel electrolyte was 7.5%, the mass fraction of lithium bisfluorosulfonylimide salt was 10%, and the mass fraction of the mixed additive was 5%; the mass ratio of 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether to butanedinitrile was 1:0.5.

[0045] Step S2: After the lithium salt is completely dissolved, polymeric monomer pentaerythritol tetraacrylate and initiator dibenzoyl peroxide are added to the solvent, and the gel electrolyte precursor solution is obtained by fully stirring. In the gel electrolyte raw materials, the mass fraction of pentaerythritol tetraacrylate is 5%, and the mass fraction of dibenzoyl peroxide is 0.1%; the stirring speed is 500 rmp, and the stirring time is 30 minutes.

[0046] Step S3: Then, the gel electrolyte precursor is placed in a polytetrafluoroethylene bottle and reacted at 50°C for 24h to obtain an in-situ polymerized gel electrolyte.

[0047] Comparative Example 1

[0048] The difference between this comparative example and Example 1 is that no mixed additive is added in the preparation of the gel electrolyte, i.e., no 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and succinonitrile is added. Other steps and materials are the same as those in Example 1.

[0049] Comparative Example 2

[0050] The difference between this comparative example and Example 1 is that no fluoroether compound is added in the preparation of the gel electrolyte, i.e., no 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is added. Other steps and materials are the same as those in Example 1.

[0051] Comparative Example 3

[0052] The difference between this comparative example and Example 1 is that no succinonitrile is added in the preparation of the gel electrolyte, and only 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is added.

[0053] Performance test:

[0054] The gel electrolytes obtained in Examples 1-3 and Comparative Examples 1-3 are assembled into stainless steel / gel electrolyte / stainless steel batteries for ion conductivity testing.

[0055] Among them, the ion conductivity is tested by the alternating current impedance method, and the battery with a stainless steel / gel electrolyte / stainless steel structure is used. The ion conductivity is calculated by the formula σ = d / (R b S), wherein d represents the thickness of the gel electrolyte, S represents the contact area with the stainless steel sheet and the polymer electrolyte membrane, and R b represents the bulk impedance measured by the alternating current impedance method. The obtained results are shown in Table 1.

[0056] Table 1 Ion conductivity test results

[0057] Item 25 °C Ionic conductivity σ (mS / cm) -10 °C Ionic conductivity σ (mS / cm) Example 1 6.01 2.66 Example 2 6.12 2.53 Example 3 6.39 2.83 Comparative Example 1 4.66 2.02 Comparative Example 2 5.33 1.88 Comparative Example 3 4.98 2.77

[0058] As shown in Table 1, the room temperature ionic conductivity and low temperature ionic conductivity of Examples 1-3 are higher than those of Comparative Examples 1-3.

[0059] The positive electrode sheet was cut into 4x4cm, and was soaked in the gel electrolyte precursor solution obtained in Examples 1-3 and Comparative Examples 1-2 respectively to perform the climbing test, and the uniform soaking time was 60s, the soaking effect of different precursor solutions was compared, and the obtained results are shown in Table 2.

[0060] Table 2: Climbing test results

[0061] Item Climbing height of electrolyte (mm) Example 1 3.29 Example 2 3.33 Example 3 4.37 Comparative Example 1 1.25 Comparative Example 2 1.82 Comparative Example 3 3.37

[0062] As can be seen from Table 1 and Table 2, compared with Comparative Example 1, the room temperature and low temperature ionic conductivity of Examples 1-3 are significantly improved, and the precursor solution has good soaking effect, which indicates that the gel electrolyte mixed additive of the present application can effectively reduce the viscosity of the gel electrolyte precursor solution and promote the transmission of lithium ions at room temperature and low temperature. Comparative Example 2 also shows good room temperature ionic conductivity, but the low temperature performance is relatively poor, which is mainly due to the fact that butanedinitrile optimizes the ion transmission performance of the electrolyte, but its high melting point limits its low temperature performance.

[0063] The present application proposes a gel electrolyte precursor containing butanedinitrile additive and in-situ polymerization gel electrolyte, the additive is mixed by butanedinitrile and fluorine ether compound, has the characteristics of low melting point and low viscosity, can be used to improve the low temperature performance and soaking property of gel electrolyte, and promote the room temperature and low temperature ion transmission. The gel preparation method is simple, only needs to be mixed to be quickly dissolved, and is compatible with the existing in-situ polymerization process, and can be directly applied to the existing battery production process. In addition, the mixed additive has inherent flame retardancy, which has potential positive effect on improving safety. Overall, the additive can significantly improve the inherent defects of the existing gel electrolyte and improve its comprehensive performance.

[0064] The above examples only express several embodiments of the present application, and the description is more specific and detailed, but it cannot be understood as a limitation on the scope of the present patent. It should be noted that for ordinary skilled persons in the art, without departing from the concept of the present application, a number of modifications and improvements can be made, which are within the scope of the present application. Therefore, the protection scope of the present patent should be subject to the appended claims.

Claims

1. A gel electrolyte characterized by, The raw materials of the gel electrolyte include polymer monomers, liquid electrolyte, mixed additives, initiator; the mixed additives include butanedinitrile and fluoroether compound; the liquid electrolyte includes lithium salt and organic solvent.

2. The gel electrolyte according to claim 1, wherein The mass of the mixed additives accounts for 1-10% of the mass of the raw materials of the gel electrolyte.

3. The gel electrolyte according to claim 2, wherein In the mixed additives, the mass ratio of the fluoroether compound to the butanedinitrile is 1:0.5-2.

4. The gel electrolyte of claim 1, wherein The fluoroether compound includes one or a mixture of several of 1,1,2,2-tetrafluoroethyl methyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

5. The gel electrolyte of claim 1, wherein The polymer monomer is an acrylate monomer.

6. The gel electrolyte of claim 1, wherein The mass of the polymer monomer accounts for 2-50% of the mass of the raw materials of the gel electrolyte.

7. The gel electrolyte of claim 1, wherein The organic solvent is a carbonate solvent.

8. A method for producing a gel electrolyte, characterized by, The method comprises the following steps: S1: uniformly mixing the organic solvent, lithium salt and mixed additives to form a mixed solution; S2: uniformly mixing the mixed solution with the polymer monomers and initiator; S3: heating and polymerizing the mixed solution obtained in step S2 to obtain the gel electrolyte according to any one of claims 1-7.

9. The method of claim 8, wherein the gel electrolyte is prepared by adding the electrolyte solution to the polymer solution, and then stirring the mixture at a temperature of 20 to 30°C for 1 to 3 hours. In step S3, the heating and polymerization conditions are: the temperature is controlled at 40-75℃, and the time is kept for 6-24h.

10. A gel lithium-ion battery, characterized by, The method comprises the gel electrolyte according to any one of claims 1-7.

Citation Information

Patent Citations

  • Flame-retardant cross-linked PDOL gel electrolyte and preparation method and application thereof

    CN119133593A